Analisis Hadis tentang Praktik Menggantungkan Doa pada Balita: Studi Kasus di Desa Janji, Labuhanbatu - Harahap, Ikhall Ahmad Fauzan; Rambe, Uqbatul Khoir (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
The practice of hanging prayers on infants is a tradition observed in Desa Janji, believed to offer spiritual protection. However, with the evolution of Islamic scholarship and modern thought, questions have arisen regarding the legitimacy of this practice based on hadith. This study aims to investigate whether the practice is grounded in authentic hadith. A descriptive qualitative method was used, with data collected through observations and interviews with five respondents. Takhrij al-Hadith was applied to assess the validity of the related hadith. The findings indicate that the hadith holds the status of Hasan-Shahih Lighairih, despite one narrator, Muhammad bin Ishaq, receiving criticism as a Mudallis and Mu’an’an. Nevertheless, supporting narrations strengthen the hadith, elevating its reliability as evidence (hujjah). In conclusion, the practice of hanging prayers on infants is permissible as long as the prayers are not considered talismans. This study contributes to addressing public concerns about the legal basis of this practice based on hadith analysis.Abstrak: Praktik menggantungkan doa pada tubuh balita merupakan tradisi yang dijalankan oleh masyarakat Desa Janji untuk perlindungan spiritual. Seiring berkembangnya kajian Islam dan modernitas, muncul pertanyaan terkait legitimasi praktik ini berdasarkan hadis. Penelitian ini bertujuan untuk menilai dasar hadis yang mendasari praktik tersebut. Menggunakan metode kualitatif deskriptif, data dikumpulkan melalui observasi dan wawancara dengan lima responden. Takhrij al-hadith digunakan untuk menganalisis validitas hadis. Hasil menunjukkan bahwa hadis terkait berstatus Hasan-Shahih Lighairih, meskipun perawi Muhammad bin Ishaq mendapat kritik sebagai Mudallis dan Mu’an’an. Namun, hadis ini diperkuat oleh riwayat lain, sehingga dapat dijadikan hujjah. Kesimpulannya, praktik menggantungkan doa pada tubuh balita diperbolehkan selama tidak diyakini sebagai jimat. Penelitian ini membantu menjawab keraguan masyarakat mengenai legalitas praktik tersebut berdasarkan analisis hadis.